IMPLEMENTASI KEBIJAKAN TATA CARA PEMBUKAAN LAHAN BAGI MASYARAKAT DALAM PENANGANAN KEBAKARAN HUTAN DAN LAHAN (KARHUTLA) DI KABUPATEN SINTANG PROVINSI KALIMANTAN BARAT - Selvia Junita Praja; Margaretha Rumbekwan; Rio Noperando (ipdn, 2020)
Forest and Land Fires in Sintang Regency Always occur every year with unstable conditions, where Forestand Land Fires have a very detrimental impact on the Community and the Government of Sintang, so that the Government of Sintang District issued Sintang District Regulations Number 57 of 2018 concerning LandClearing Procedures for the Community. In this regard, researchers are interested in conducting researchunder the title